A Novel Ultrasonic Sampling Penetrator for Lunar Water Ice in the Lunar Permanent Shadow Exploration Mission - Yinchao Wang; Zihao Yin; Chenxu Ding; Fei Liu; Weiwei Zhang; Lin Zu; Zhaozeng Gao; Guanghong Tao; Suyang Yu (Aerospace)
This paper presents an ultrasonic sampling penetrator with a staggered-impact mode, which has been developed for the extraction of lunar water ice. A comparison of this penetrator with existing drilling and sampling equipment reveals its effectiveness in minimizing disturbance to the in situ state of lunar water ice. This is due to the interleaved impact penetration sampling method, which preserves the original stratigraphic information of lunar water ice. The ultrasonic sampling penetrator utilizes a single piezoelectric stack to generate the staggered-impact motion required for the sampler. Finite element simulation methods are employed for the structural design, with modal analysis and modal degeneracy carried out. The combined utilization of harmonic response analysis and transient analysis is instrumental in attaining the staggered-impact motion. The design parameters were then used to fabricate a prototype and construct a test platform, and the design’s correctness was verified by the experimental results. In future sampling of lunar water ice at the International Lunar Research Station, the utilization of the ultrasonic sampling penetrator is recommended.